Comparison of plasma and CSF biomarkers in predicting cognitive decline. Issue 11 (2nd October 2022) - Aschenbrenner, Andrew J.; Li, Yan; Henson, Rachel L.; Volluz, Katherine; Hassenstab, Jason; Verghese, Philip; West, Tim; Meyer, Matthew R.; Kirmess, Kristopher M.; Fagan, Anne M.; Xiong, Chengjie; Holtzman, David; et al.
Abstract: Objectives: Concentrations of amyloid‐β peptides (Aβ42/Aβ40) and neurofilament light (NfL) can be measured in plasma or cerebrospinal fluid (CSF) and are associated with Alzheimer's disease brain pathology and cognitive impairment. This study directly compared plasma and CSF measures of Aβ42/Aβ40 and NfL as predictors of cognitive decline. Methods: Participants were 65 years or older and cognitively normal at baseline with at least one follow‐up cognitive assessment. Analytes were measured with the following types of assays: plasma Aβ42/Aβ40, immunoprecipitation‐mass spectrometry; plasma NfL, Simoa; CSF Aβ42/Aβ40, automated immunoassay; CSF NfL plate‐based immunoassay. Mixed effects models evaluated the global cognitive composite score over a maximum of 6 years as predicted by the fluid biomarkers. Results: Analyses included 371 cognitively normal participants, aged 72.7 ± 5.2 years (mean ± standard deviation) with an average length of follow‐up of 3.9 ± 1.6 years. Standardized concentrations of biomarkers were associated with annualized cognitive change: plasma Aβ42/Aβ40, 0.014 standard deviations (95% confidence intervals 0.002 to 0.026); CSF Aβ42/Aβ40, 0.020 (0.008 to 0.032); plasma Nfl, −0.018 (−0.030 to −0.005); and CSF NfL, −0.024 (−0.036 to −0.012). Power analyses estimated that 266 individuals in each treatment arm would be needed to detect a 50% slowing of decline if identified by abnormal plasma measures versus 229 for CSF measures. Interpretation: Both plasma and CSF measures of Aβ42/Aβ40 and NfL predicted cognitive decline. A clinical trial that enrolled individuals based on abnormal plasma Aβ42/Aβ40 and NfL levels would require only a marginally larger cohort than if CSF measures were used.